Impelementasi Evaluasi Program Pendidikan Karakter Di SMP Negeri 2 Binjai - Yuni Syafriani; Suci Ramadhani; Fella Annisa Harahap; Amar Khairi Ahmad; Yogi Andrian; Imam Amirmusthofa; Inom Nasution (Lembaga Pengembangan Kinerja Dosen, 2023)
Character education applied aims to improve the quality and result of education implementation that leads to the achievement of integrated and balanced students’ character building according to the graduate competence standard. In order to measure the success of character education, an integrated evaluation is conducted which covers: 1) context evaluation that comprises of policy basis, needs’ perception and purpose of character education program; 2) input evaluation that comprises of strategic planning, organizational structure design, implementation procedure, and resources availability of character education program; 3) process evaluation that comprises of coordination, implementation, and supervision of the character education program enforcement; and 4) product evaluation which comprises of the achievement and impact of character education program. The evaluation of character education program is conducted in order to give reinforcement, improvement, and to measure the success of the character education program implementation carried out by education institution.